Peran Hard Skill dan Soft Skill pada Peningkatan Kesiapan Kerja bagi Mahasiswa - Wilujeng Aprillia; Dyah Wulansari (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to provide a comparison of the important role of hard skills and soft skills in improving work readiness for students to be ready and able to enter the world of work. The importance of the role of these two components in students provides readiness for students to compete healthily in companies after entering the world of work. A significant balance in these two components can support student comfort when in the world of work. The important role of work readiness and characteristics to the benefits of work readiness. In the world of work, you must have a mentality and understanding of other people which are included in soft skills, while hard skills themselves play a role in facilitating the completion of work if students are able to master hard skills, then completing work will be easier and will get results according to expectations.